Biosynthesized Silver Nanoparticles Encapsulated in a Poly(vinyl alcohol) Matrix: Dielectric and Structural Properties. Issue 47 (14th December 2022) - Bulla, Soumya S.; Bhajantri, R. F.; Chavan, Chetan; Sakthipandi, K.
Abstract: In the present investigation, silver (Ag) nanoparticles were prepared employing green synthesis from the aqueous leaves extract of Cyperus rotundus (CR) plant at ambient temperature in less reaction time. A preliminary phytochemical analysis test was performed, and it has been revealed that the extract comprised bioactive components such as alkaloids, phenols, and terpenoids, among others. For average size, the morphology (spherical shape) and purity of the nanoparticles were characterized using scanning electron microscopy (SEM, 358 nm) with energy‐dispersive X‐ray (EDX), dynamic light scattering (27 nm), high‐resolution transmission electron microscopy (3.9 nm), and selected area electron diffraction (SAED) pattern methods. Without any extra peaks in the EDX spectrum, the produced Ag nanoparticles were confirmed to be pure. In addition, the solvent‐casting approach has been used to encapsulate a different weight fraction of biosynthesized Ag nanoparticles (CR−Ag−NPs) in a polyvinyl alcohol (PVA) matrix. By using UV‐visible, FTIR spectroscopy, and SEM, we were able to characterize the synthesized CR−Ag−NPs as well as their composite (PVA) films, and we were able to compare the results with those of pristine PVA. The effects of doping with CR−Ag−NPs on structural and morphological changes of PVA were studied. Impedance studies, including dielectric constant, dielectric loss, tangent loss, and AC conductivity, revealed that incorporating CR−Ag−NPs into the PVA matrix impacts the electrical properties of PVA. This study showed that the synthesized nanoparticles had a spherical shape with entangled biocomponents and were encapsulated within the PVA polymer matrix, indicating that CR−Ag−NPs can be used in various applications (wound healing). Abstract : In this study, silver (Ag) nanoparticles were prepared employing green synthesis from the aqueous leaves extract of Cyperus rotundus (CR) plant at ambient temperature in less reaction time, followed by primarily phytochemical analysis. Phenols are a source of natural antioxidants that could be necessary for the production of Ag NPs. Techniques such as SEM (358 nm), HRTEM (4 nm), and DLS (27 nm) were used to determine the average size, shape, and purity. In addition to this, the solvent‐casting approach has been used to encapsulate a different weight fraction of biosynthesized Ag nanoparticles (CR−Ag−NPs) in a polyvinyl alcohol (PVA) matrix. The effects of doping with CR−Ag−NPs on structural, optical and morphological changes of PVA were studied. Impedance studies, including dielectric constant, dielectric loss, tangent loss, and AC conductivity, revealed that incorporating CR−Ag−NPs into the PVA matrix impacts the electrical properties of PVA. This study showed that the synthesized nanoparticles had a spherical shape with entangled biocomponents and were encapsulated within the PVA polymer matrix, indicating that CR−Ag−NPs can be used in various applications.